Financial Crisis in Management Stress: From the Perspective of Crisis Anxiety of Others - Liu, Bin; Zhu, Jing; Su, Fangguo; Wen, Bin; Wu, Yingqi (Frontiers in Psychology, 2022)
The crisis anxiety of others is a phenomenon that goes hand in hand with the spread of the occupational health pandemic. It is becoming increasingly important to better understand its emergence process, especially in the era of greater uncertainty. This study aims to examine the impact of the external financial crisis on managerial stress among financial employees. The sample consists of 347 senior managers and financial employees from companies in China. The empirical analysis shows that external financial crises have significant effects on anxiety levels, especially external corporate crisis, debt crisis and growth crisis both have mediating effect on the relationship between anxiety level and and pressure management and the relationship between external financial crisis and pressure management. This study explores the rules for the emergence of anxiety among corporate managers and expands the scope of environmental factors that need to be discussed in the study of corporate financial management. This study provides theoretical implications for the psychological study of Financial Management and practical implications for corporate financial management.